Konsultasi dan Pelatihan Penerapan Kaizen pada Lantai Produksi untuk Meningkatkan Kinerja di PT Kahatex, Bandung - Leony, Florence; Arisandhy, Vivi; Suhada, Kartika; Suhandi, Victor; Heryanto, Rainisa Maini; Liputra, David Try; Santoso, Warren Evander; Suwandi, Nadia Natalia; Banjarnahor, Dedi Marcell; Manuela, Rheakova Sarita; Paganta, Dioren Tri (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
PT Kahatex is a textile company that has implemented the Kaizen concept in its production process. However, in practice, partners still encounter obstacles, namely in terms of the participation of all employees in making changes and determining the right methods that are in line with the Kaizen philosophy in solving problems on the production floor. This community service activity in the form of training was carried out to provide understanding and direction to partners regarding real examples of the application of easy-to-do methods on the production floor in relation to continuous improvement. The community service activity was carried out from January 8 to 26, 2024, which consisted of the preparation and implementation stages of the training. The community service team consisted of 6 lecturers and 5 students, while the training participants consisted of 20 PT Kahatex employees. The result of this training activity was an increase in the percentage of participants who fully understand the Kaizen material and the benefits of its application as well as 5W1H and examples of its application, from initially between 15% - 25% to between 60% - 75%.